Optimizing hydrogen production from the Landfill Leachate by electro-coagulation technique - Che Man, Hasfalina; Xie, Chai Yun; Md. Yunos, Khairul Faezah; Mohammed, Abdulsalam; Hamzah, Muhammad Hazwan (Sixscientia Resources, 2020)
The loss and impact of non-renewable fossil energy on global warming concerns are prompting to intensive research to find viable, less emissions-oriented alternative energies. The present work aims to study the potential of hydrogen gas production (for renewable energy) by electrocoagulation process from landfill leachate. The Design-Expert software for response surface methodology (RSM) was used to investigate the process variables in the hydrogen production system. The effects of three independent variables; namely pH (4-8) and voltage (3-9 V), using different types of electrodes (Al, Fe, and Ni) were studied. At the optimal condition of voltage 9V and initial pH 6 at 20 minutes, the Al electrode recorded an upturn maximum H2 yield of 697 ppm, while 554 and 551 ppm were obtained with Ni and Fe electrode, respectively. Moreover, the coefficient of determination (R 2) showed a good relationship between actual and expected results.